Melacak Argumen Kesetaraan Gender dalam Kitab Uqud Al-Lujjayn - Ahmad Natsir (LPPM IAI Hasanuddin Pare-Kediri, 2019)
Discourse on gender in Indonesia often refers to figures from America, Europe and Arabia, so that there are still Eurocentric or arabisentric cases. An archipelago figure in the pre-independence era, Shaykh Ibn Umar al-Jawi al-Bantani, had composed a book that reviews the rights and obligations of a husband and wife. However, instead of getting appreciation, this book actually gets a lot of criticism because of the many narratives that still discredit women, ranging from books that make men big heads to accusations as a book that is the source of domestic violence. By using the five-angle approach study Amin Abdullah the author wants to express the big idea in the form of a gender equality narrative carried by Shaykh Nawawi al-Bantani. This paper provides a conclusion in the form of gender equality carried by Shaykh Nawawi al-Bantani contained in the rights obtained by the wife from her husband and vice versa. By carrying out the association with ma'ruf Shaykh Nawawi gives an idea of ​​how the association of husband and wife in the household.